2007
DOI: 10.2310/6620.2007.06047
|View full text |Cite
|
Sign up to set email alerts
|

Shoe Allergens: Retrospective Analysis of Cross-Sectional Data from the North American Contact Dermatitis Group, 2001-2004

Abstract: Background: Chemicals used in leather tanning, rubber processing, and/or adhesives are the most often-cited culprits in footwear dermatitis. Patch testing patients with suspected shoe dermatitis is essential for diagnosis and management.Objectives: The four goals for this study were to (1) determine the frequency of allergens associated with a shoe source in North American Contact Dermatitis Group (NACDG) patients with footwear allergic contact dermatitis; (2) compare these results to allergen frequencies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
68
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 28 publications
16
68
1
Order By: Relevance
“…Also the positivity to benzocaine has increased with age. These findings are also described by other authors (5,9,22). Indeed, benzocaine is an ester local anesthetic.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Also the positivity to benzocaine has increased with age. These findings are also described by other authors (5,9,22). Indeed, benzocaine is an ester local anesthetic.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, Warshaw et al (5) in a comparative study of patch tests results depending on the age conducted among 31942 patients, noted a decrease in the prevalence of atopy with age. This prevalence was 84.4% in younger patients (<18 years) and 36.4% at subjects aged more than 65 years (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Uter et al 7 found a significant trend for higher reactivity rates to thiuram mix and zinc diethyldithiocarbamate, but not mercapto mix, with increasing age. The higher rates to rubber accelerators may be a result of longer duration of exposure to sources in shoes 25 and gloves 26 or relatively greater exposure to rubber in medical devices (eg, support stockings).…”
Section: Topical Antibioticsmentioning
confidence: 99%
“…5 From an epidemiologic standpoint, shoe ACD has been difficult to characterize because of variation in the series of allergens tested, differing shoe manufacturing processes, and changing trends in footwear across time and regions of the world. 7,8 Despite and owing to this challenge, shoe dermatitis calls for further sustained research and better understanding because it impacts so many people.…”
mentioning
confidence: 98%